Estudo comparativo entre dois cimentos endodônticos à base de resina epóxi: citotoxicidade e detecção de biomarcadores - Silva, Agtha Christie Moreira (2018)
The objective of the present study was to detect biomarkers, as well as to evaluate and compare the cytotoxicity of Sealer Plus (MK Life, Brazil) and AH Plus (Denstply, Germany) cements. For the cytotoxic assay, the immortalized human osteoblasts of the Saos-2 lineage were incubated with the dosages of the tested materials for a period of 24 hours, one of the highlights being the use of colorimetric assays by the MTT method. In the control group, cells were exposed to the conventional cell culture medium. Data were tested in a normal distribution by the Kolmogorov-Smirnov test, and comparisons between groups were analyzed by analysis of variance (ANOVA) followed by the Kruskal-Wallis test. The P value considered significant was <0.05. For the biomarkers test, we used the Luminex immunoassay that allows the evaluation of different biomarkers in a single experiment. The targets were delineated through the Bio-Plex Pro Human Cytokine 27-Plex Immunoassay kit, the selected plate detects cytokines, chemokines and growth factors, which are involved in inflammatory processes. The data obtained by reading the plate by the Bio-Plex® MAGPIX ™ system were subjected to statistical analysis using GraphPad Prism software. The data were exposed to comparisons between groups through the student T test. The values of p <0.05; p <0.001 and p <0.001. The results showed that there was no statistically significant difference in cytotoxicity between the Sealer Plus and AH Plus tested cements and the control group (p> 0.05). The biomarkers detected statistically significant between the groups were IL-1ra, IL-8, GM-CSF and basic FGF. According to the results, IL-1Ra and IL-8 analytes present higher dosage in response to AH Plus cement, whereas Sealer Plus showed higher dosages of b-FGF and GM-CSF. It is concluded that Sealer Plus presents cytocompatibility similar to the control group, however, it is suggested a greater inflammatory potential of Sealer Plus when compared to AH Plus, in relation to the analytes studied.